Illustration guidebook of making Wayang Kulit Kelantan puppets / Nur Syahira Ain Abdul Halim and Rafuzan Jaafar - Abdul Halim, Nur Syahira Ain; Jaafar, Rafuzan (Kolej Pengajian Seni Kreatif (KPSK) UiTM Cawangan Melaka, 2023)
The purpose of writing this article is to make an illustration guidebook of The Making of Wayang Kulit Kelantan with illustrations that are easily understood by the target audience. The reason why this book was made is, in the available Wayang Kulit Kelantan Guidebook, which is still dominated by written forms which do not give knowledge to the general public about Wayang Kulit Kelantan. Approach to the design of The Making of Wayang Kulit Kelantan Guidebook design covers the design of books, Wayang Kulit character, illustrations, colors, layouts, and typography. The supporting media produced were pin badge, sticker, tote bag, and bookmark.